Raiding, trading, and feasting : the political economy of Philippine chiefdoms - Junker, Laura Lee, 1958- (University of Hawaiì Press, 1999)
As early as the first millennium A.D., the Philippine archipelago formed the easternmost edge of a vast network of Chinese, Southeast Asian, Indian, and Arab traders. Items procured through maritime trade became key symbols of social prestige and political power for the Philippine chiefly elite. Raiding, Trading, and Feasting presents the first comprehensive analysis of how participation in this trade related to broader changes in the political economy of these Philippine island societies. By combining archaeological evidence with historical sources, Laura Junker is able to offer a more nuanced examination of the nature and evolution of Philippine maritime trading chiefdoms. Most importantly, she demonstrates that it is the dynamic interplay between investment in the maritime luxury goods trade and other evolving aspects of local political economies, rather than foreign contacts, that led to the cyclical coalescence of larger and more complex chiefdoms at various times in Philippine history. A broad spectrum of historical and ethnographic sources, ranging from tenth-century Chinese tributary trade records to turn-of-the-century accounts of chiefly "feasts of merit," highlights both the diversity and commonality in evolving chiefly economic strategies within the larger political landscape of the archipelago. The political ascendance of individual polities, the emergence of more complex forms of social ranking, and long-term changes in chiefly economies are materially documented through a synthesis of archaeological research at sites dating from the Metal Age (late first millennium B.C.) to the colonial period. The author draws on her archaeological fieldwork in the Tanjay River basin to investigate the long-term dynamics of chiefly political economy in a single region. Reaching beyond the Philippine archipelago, this study contributes to the larger anthropological debate concerning ecological and cultural factors that shape political economy in chiefdoms and early states. It attempts to address the question of why Philippine polities, like early historic kingdoms elsewhere in Southeast Asia, have a segmentary political structure in which political leaders are dependent on prestige goods exchanges, personal charisma, and ritual pageantry to maintain highly personalized power bases. Raiding, Trading, and Feasting is a volume of impressive scholarship and substantial scope unmatched in the anthropological and historical literature. It will be welcomed by Pacific and Asian historians and anthropologists and those interested in the theoretical issues of chiefdoms